Financial Accounting: Information for Decisions - J.Wild John (American : McGraw -Hill, 2011)
Contets of text
With years of success in the introductory accounting market, the author team of Wild, Larson and Chiappetta is a leader in accounting instruction, technology application, and student learning. Once again, this author team responds to the market’s request for a more balanced financial and managerial (~50/50) book with a corporate approach; thus, we announce the publication of Financial and Managerial Accounting by Wild, Larson and Chiappetta. With the same innovative features as reflected in Fundamental Accounting Principles, 17e, the authors provide a balance to small and large business examples, the integration of new computerized learning tools, superior end-of-chapter materials, and highly engaging, pedagogical learning structures. The inclusion of Homework Manager and Carol Yacht’s General Ledger and Peachtree software provides students with further advantages as they strive to learn key accounting concepts and their role in business. With over 250 instructors providing us feedback and direction, the author team “reached new heights” in providing you and your students the most accessible, reliable, and instructor-friendly textbook ever. After reviewing this textbook, you will see why Financial and Managerial Accounting by Wild, Larson and Chiappetta is the best introductory financial and managerial accounting text on the market.
Keywords: Financial Accounting; Kế toán